Nitrogen dynamics and balance in intensified rainfed lowland rice-based cropping systems - Tripathi, B.P.; Ladha, J.K.; Timsina, J.; Pascua, S.R. (Wiley, 1997)
Nitrogen dynamics and balances in intensive and diversified lowland rice (Oryza sativa L.)‐based cropping systems that receive heavy fertilization, tillage, and irrigation have not been explored. Such information is essential to improve the efficiency of N fertilizer, an input based on a nonrenewable energy resource and whose oxidized products pose hazards to human health and the environment. Field experiments at an experimental farm on an Inceptisol and in two farmers' fields, one with an Inceptisol and one with a Vertisol soil, quantified (i) NO‐3‐N and NH+4‐N in different soil layers in relation to water‐filled pore spaces (WFPS), (ii) N balance, and (iii) systems‐level N efficiencies in several cropping patterns. Nitrate‐N and NH+4‐N were quantified monthly from July 1993 to June 1994. The WFPS remained <0.80 mL mL‐1 in the beginning of the wet season and throughout the dry season that enhanced nitrification. Ammonium‐N in the 100‐cm layer was 20 to 40 kg ha‐1 in the wet season and <10 kg ha‐1 in the dry season. Nitrate‐N, however, ranged from 27 to 54 and from 67 to 195 kg ha‐1 in the two seasons; it was higher in farmers' fields (192–195 kg ha‐1) than in the experimental farm (67–112 kg ha‐1). Total N loss was 34 to 549 kg ha‐1 across sites, with the largest in rice‐sweetpepper (Capsicum annuum L. var. annuum) and rice‐tomato (Lycopersicon esculentum Miller). Despite a lack of a consistent trend in N efficiency among the different cropping systems, it was higher with tobacco (Nicotiana tabacum L.) and garlic (Allium sativum L.). There appears an opportunity to grow a NO‐3 catch crop during the dry‐wet transition in rice‐sweetpepper and rice‐tomato systems to capture and recycle soil NO‐3‐N.